I have this code, where k is the alias of j. I set j /1*10/

My intention is to write a code which is like this:

for j=1:Jn

for k=1:j

sum = sum + k*(x(k) - x(k-1))

end

end

76 utility … f =e= In*sum(j, ((lambda*(1 - (sqrt(sum((l,t), power((y(j,

l,t) - (sum(k $ (ord(k) <= ord(j) and ord(k) >= 2), k*(x(k) - x(k-1))) +

**** 148
1*x('1'))/zeta*eta(j,l,t)),2)))/sqrt(sum((l,t), power(y(j,l,t),2)))))) -
x(j))*p(j));
86 limit1b(j,l,t) (ord(j) gt 1) … (sum(k $ (ord(k) <= ord(j) and ord(k)

= 2), k*(x(k) - x(k-1))) + 1*x(‘1’))/zeta =l= y(j,l,t) ;

**** $148

Why does this error occur?